Before and After Lecturers’ Perceptions on the Implementation of Literature-based Reading Instruction: Advantages and Disadvantages - Baharuddin, Andi Farid; Mardiani; Fentry Hernaningsih Ruing (Institut Agama Islam Negeri Palopo, 2024)
Some literary experts conveyed that literature is recommended to be utilized in language teaching especially if the lecturers are knowledgeable on literary integration for language teaching. Experts define the literary use in language teaching as literature-based instruction (LBI). Hence, this research aimed at studying the lecturers’ perception towards literature-based instructional approach before and after implementing it in the reading class. In exploring the issues, this research investigated two research questions (RQs): a) what are the lecturers’ perceptions towards LBI before implanting it in a reading classroom? b) What are the lecturers’ perceptions towards LBI after implanting it in the reading classroom? Furthermore, a qualitative method with a case study approach is employed in this study. The participants consisted of two lecturers who taught in the English education department at Universitas Sawerigading Makassar. To gain the data, the researchers utilized a semi-structured interview which was adapted from McDiarmid's (1995) interview model. All the collected data were furthermore analyzed using Braun and Clarke's (2006) thematic analysis. The results showed that both lecturers' perceptions were varied for both before and after implementing the LBI due to different academic background and experience. The lecturers who’s academic and research interest were focusing on literary studies would have better perception towards LBI. Definitely, with an eye-eagle vision towards LBI, the lecturers could potentially touch many aspects and values in his/her literary teaching as the advantages of LBI.